RNF219/α‐Catenin/LGALS3 Axis Promotes Hepatocellular Carcinoma Bone Metastasis and Associated Skeletal Complications. Issue 4 (31st December 2020) - Zhang, Shuxia; Xu, Yingru; Xie, Chan; Ren, Liangliang; Wu, Geyan; Yang, Meisongzhu; Wu, Xingui; Tang, Miaoling; Hu, Yameng; Li, Ziwen; Yu, Ruyuan; Liao, Xinyi; et al.
Abstract: The incidence of bone metastases in hepatocellular carcinoma (HCC) has increased prominently over the past decade owing to the prolonged overall survival of HCC patients. However, the mechanisms underlying HCC bone‐metastasis remain largely unknown. In the current study, HCC‐secreted lectin galactoside‐binding soluble 3 (LGALS3) is found to be significantly upregulated and correlates with shorter bone‐metastasis‐free survival of HCC patients. Overexpression of LGALS3 enhances the metastatic capability of HCC cells to bone and induces skeletal‐related events by forming a bone pre‐metastatic niche via promoting osteoclast fusion and podosome formation. Mechanically, ubiquitin ligaseRNF219‐meidated α ‐catenin degradation prompts YAP1/ β ‐catenin complex‐dependent epigenetic modifications of LGALS3 promoter, resulting in LGALS3 upregulation and metastatic bone diseases. Importantly, treatment with verteporfin, a clinical drug for macular degeneration, decreases LGALS3 expression and effectively inhibits skeletal complications of HCC. These findings unveil a plausible role for HCC‐secreted LGALS3 in pre‐metastatic niche and can suggest a promising strategy for clinical intervention in HCC bone‐metastasis. Abstract : Hepatocellular carcinoma (HCC)‐secreted LGALS3 induces osteolytic bone metastasis (BM) via promoting osteoclast fusion and podosome formation. Mechanistically, RNF219‐mediated α ‐catenin degradation results in YAP1/ β ‐catenin‐dependent epigenetic modifications on LGALS3 promoter, eliciting in LGALS3 upregulation in HCC. Blocking YAP1/ β ‐catenin complex formation on LGALS3 promoter via verteporfin reduces LGALS3 expression and effectively inhibits HCC bone‐metastasis (HCC‐BM), which represents a potential strategy for HCC‐BM clinical treatment.